Descentralização da Competência Da Gestão Ambiental No Amazonas: aspectos legais e práticos - Freitas, Laís Rejane de Carvalho (2011)
The strength of the Municipalist movement, which advocated greater powers and autonomy for municipalities, at the 1988 Brazilian Constitution, was responsible for the profile of the federal state which appears in the current Magna Carta, which reads that the Federative Republic of Brazil is "formed by the indissoluble union of states and municipalities and the Federal District." In fact, for the first time in the Brazilian constitutional history were provided to municipalities relevant assignments, including environmental matters. However, the competence of the three federal entities is mixed up, including with regard to the substantive jurisdiction of the municipalities, because in spite of the Constitution had assured them many tasks, it was not careful to predict the transfer of the financial and technical counterpart, necessary for the effective performing of all tasks that were granted. As a result, the performance of the Brazilian municipalities is shy, being not possible to give proper effect to all existing federal and regional programs, especially in environmental matters. A viable alternative to solve, but all at least in some sectors, the impossibility to implement the programs pertaining to the municipalities, consists in the cooperation between the members of the Federation, whether through partnerships or consortia, which even results in an increase of the sphere of influence of the local democracy.